Tuli Mengaji Goes Digital Instagram as a Cooperative Communication and Social Marketing Strategies for Inclusive Islamic Philanthropy - Ulva Lathifah; Rocky Prasetyo Jati (Yayasan Darussalam Bengkulu, 2026)
The digital transformation of Islamic philanthropy has created new opportunities for inclusive social engagement, yet the strategic use of social media platforms as channels integrating cooperative communication and social marketing remains underexplored, particularly regarding disability-inclusive programs. This study examines how LAZNAS PPPA Daarul Qur'an leverages Instagram as a cooperative communication and social marketing channel to communicate the